Collaborating with Communities and Higher Education to Address the Health-care Needs of Individuals with Disabilities in Ecuador - Cech, Donna J.; Alvarado, Zully J. (Frontiers in Public Health, 2017)
Individuals with disabilities experience inequities in access to health care, education, employment and social inclusion. Causes for Change International (CCI), a non-governmental Organization (NGO), using a community based rehabilitation (CBR) approach has worked for 20 years to build self-sufficiency, improve health care services, and education for women, children, and persons with disabilities in Ecuador. CCI initially addressed health; advocacy for individuals with disabilities; and promoted educational opportunities for children with disabilities, starting in one rural community. CCI’s outreach has expanded through Ecuador’s coastal provinces, Andean provinces and Galapagos Islands. CCI also focused on local health care workforce development, developing employment skills for individuals with disabilities and social inclusion for this population. CCI collaborated with local organizations, government and universities to provide resources, managed by local leadership. Key program elements of the CCI approach include: 1) develop trust between CCI, local communities, local agencies and government; 2) empower local groups to assume leadership and sustain programs. 3) support communities and groups invested in developing self-sufficiency; and 4) strengthen collaborations and partnerships between local and international organizations, universities, and government agencies. Key lessons learned by CCI are to be supportive of cultural differences; understand that limited financial and material resources may limit the program development; recognize it is difficult not to foster dependent relationships with communities and appreciate the importance of working with and within the host country’s governmental systems. CCI is expanding its service base to other regions of Ecuador, and is focusing on development of the Ecuadorian health care workforce and social inclusion opportunities for individuals with disability. The efforts of a small NGO have helped build community self-sufficiency in meeting the health care and rehabilitation needs of all Ecuadorian citizens and a greater awareness of the abilities and potential contributions of individuals with disabilities.